Graduate STEM students as role models for high school students - Topliceanu, Ana-Maria; McCance, Katherine R.; Blanchard, Margaret R.; Sollinger, Jennifer (Frontiers in Education, 2025)
IntroductionSTEM graduates are important to U.S. research development and innovation, adding diverse perspectives and talents to communities and the academy, and enhancing the financial stability of universities. Graduate STEM students’ work on funded research occasionally engages them in outreach opportunities with K-12 schools and students. Yet, few graduate students participate in professional development that prepares them for these roles.MethodsThis exploratory, descriptive case study chronicles the experiences of eight graduate STEM students (six international and two domestic) who visited high school classrooms, via Zoom, as part of a federally funded sustainability project. This study investigated the factors graduate STEM students considered most important when planning and implementing their Zoom outreach visits, what they perceived as the supports, benefits, and challenges, and in what ways their Zoom visits and reflections correspond to the Motivational Theory of Role Modeling.ResultsThe findings demonstrate graduate students’ focus on engaging students, the relevance of science to society, and job opportunities in STEM fields. Graduate students perceived challenges associated with making the complex academic language and research understandable to high school students and felt supported by university team members and high school teachers.DiscussionImplications for role models and professional development for graduate STEM students are discussed, along with novel contributions to the theoretical framework.